Synthetic and Semi-Synthetic Microplastic Ingestion by Mesopelagic Fishes From Tristan da Cunha and St Helena, South Atlantic - McGoran, Alexandra R.; Maclaine, James S.; Clark, Paul F.; Morritt, David (Frontiers in Marine Science, 2021)
Mesopelagic fishes were sampled around Tristan da Cuhna and St Helena in the South Atlantic from the RRS Discovery at depths down to 1000 m. Sampling was part of the Blue Belt Programme, a marine survey of British Overseas Territories funded by the UK Government. Thirteen species of mesopelagic fishes identified from 30 specimens were compared with two species (two specimens) collected from rock pools or surface water near the shore. The digestive tracts of all fishes were examined for microplastics. Additionally, one specimen of Opostomias micripnus (Günther, 1878) was analysed after recovery from the stomach of a commercially fished species, Hyperoglyphe antarctica (Carmichael, 1819). One specimen of Anoplogaster cornuta (Valenciennes, 1833) was found to have ingested a bearded sea devil (Linophryne sp.), a cock-eyed squid (Histioteuthis sp.), a bolitaenid octopus, Japetella diaphana (Hoyle, 1885), remains of unidentifiable fish, crustaceans and possibly salps. These prey items were also examined for microfibres. Both Histioteuthis sp. and Linophyrne sp. had ingested fibres and these were considered “ingested particles” for A. cornuta. Neither shallow water dwelling species had ingested microplastics, whilst 11 of the 13 studied mesopelagic species were found to be contaminated. Overall, 66.7% of mesopelagic fishes were found to contain microfibres. Anthropogenic fibres were common especially viscose, a semi-synthetic material which is associated with sanitary products as well as other items.